Impact of undulation on magneto-free convective heat transport in an enclosure having vertical wavy sides. (October 2021) - Fayz-Al-Asad, Md.; Nur Alam, Md.; Rashad, A.M.; Manirul Alam Sarker, Md.
Abstract: A computational study has been prepared to explore the impact of undulation on magneto-free convection heat transport in a wavy enclosure bounded by vertical wavy sides and maintaining isothermal boundary condition at the bottom walls while the top wall being adiabatic. Relevant governing equations were discretized by utilizing GWR process of finite element technique. Impact of Hartmann number (0 to 50), the number of waves (between 1 and 3), and Rayleigh number (between 10 3 and 10 6 ) at Pr = 0.71 on the flow phenomena and temperature behavior were studied using streamlines, isotherms, wave effectiveness, mean fluid temperature, and average Nusselt numbers. The numerical outcomes exhibit that the evolution of heat transport in the wavy cavity boosts by ascending the number of undulation ( λ = 3) and Rayleigh number. The outcomes are verified associating with the published studies.